Tangled webs : how false statements are undermining America : from Martha Stewart to Bernie Madoff - Stewart, James B. (Penguin Press, 2011)
America faces a crisis--an epidemic of perjury and false statements occurring at the highest levels of business, politics, sports, and culture. How and why has this happened? What are the consequences? What can be done? Here, Pulitzer Prize-winning author James B. Stewart applies his investigative reporting and storytelling skills to four dramatic cases, all involving people at the top of their fields: Martha Stewart, I. Lewis "Scooter" Libby, Barry Bonds, and perhaps the most notorious liar in financial history, Bernard Madoff. Stewart draws on extensive interviews with participants, many speaking here for the first time, and previously undisclosed documents and transcripts to show how such celebrated and successful role models found themselves accused of lying--with devastating consequences, not just for them but for an ever-widening circle that ultimately includes everyone who cares about the truth.--From publisher description.